Breaking Strength of Pedicel as an Index of Grain-Shattering Habit in Autotetraploid and Diploid Buckwheat (Fagopyrum esculentum Moench.) Cultivars - Shinya Oba; Atsuko Ohta; Fumihiro Fujimoto (Plant Production Science, 1999)
The grain-shattering habit was compared among diploid and autotetraploid cultivars of common buckwheat (Fagopyrum esculentum Moench.). In the first experiment, one diploid and one autotetraploid cultivar were grown in the field, and the number of grains shed naturally by wind or rain, and the number of grains detached by threshing the plants (by dropping from 1 m height onto a concrete floor, five times) were measured to evaluate grain shattering. The number of the naturally shed grains in the field was higher in the diploid than in the autotetraploid cultivar, although the number of grains detached by threshing was not different between the two cultivars. In another set of experiments, breaking bending strength and breaking tensile strength of pedicels were measured as indices of grain-shattering habit to examine the difference in shattering among two autotetraploid and four diploid cultivars (two summer types and two autumn types). They were grown in summer and autumn seasons to examine the environmental effect on grain shattering. Both breaking strengths were about two times higher in the autotetraploid cultivars than in the diploid cultivars. The breaking strength was well correlated with the diameter of pedicels. The values of grain-shattering resistance traits obtained in the autumn cropping season were higher than those obtained in the summer cropping season.